Princess Posey and the monster stew - Greene, Stephanie (Greene, Stephanie. Princess Posey, first grader, 2012)
First-grader Posey and her friends are excited about Halloween, but also a little nervous about trick-or-treating and eating Miss Lee's monster stew.